¿Por qué fue reclutada la turma Salluitana en Salduje? - Pina Polo, Francisco (Gerión. Revista de Historia Antigua, 2003)
The so-called “Bronze from Ascoli” contains the grant by Pompeius Strabo, in the context of the Bellum Sociale, of the Roman citizenship to the members of the turma Salluitana, horsemen coming from several towns in the Ebro valley (Hispania Citerior). The turma Salluitana was recrouited in Salduie-Salduvia because this town was a central place in the area and was the only town mentioned in the Ascoli inscription next to the Ebro river, and was therefore endowed with an embankment that made easier the transfer of the troops to Italy.